Undiscovered Country : A Novel - Enger, Lin (Book collections on Project MUSE., 2020)
Now in paperback-a bold reinvention of Shakespeare's Hamlet and a hair-bristling story of betrayal, revenge, and the possibilities of forgiveness On a cold November afternoon in northern Minnesota, seventeen-year-old Jesse Matson finds his hunting partner-his father-sprawled on the forest floor, dead of a rifle wound. Authorities rule it a suicide, but Jesse is not convinced. Haunted by the ghost of his dad, and compelled by recently unearthed secrets, he is forced to wrestle with questions of justice and retribution even as he tries to hold his family, and himself, together.